Pengaruh Capital Intensity Dan Likuiditas Terhadap Agresivitas Pajak Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Sektor Energi Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2021 - Rofiqoh Nurfajriah Modjo; Mulyadi Mulyadi; Panata Bangar Hasioan Sianipar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
This study aims to examine and analyze the effect of capital intensity and liquidity on tax aggressiveness and to test and analyze the effect of profitability in moderating capital intensity and liquidity on tax aggressiveness in energy sector companies listed on the Indonesian stock exchange for the 2018-2021 period. The type of research used is quantitative. The population in this study are 80 companies. The sample selection in this study used a purposive sampling method with a total sample of 25 companies for 4 years so that the total sample used was 100 data. The type of data used is secondary data obtained from the company's annual financial reports for the 2018-2021 period. The results of this study indicate that partially capital intensity has a significant effect on tax aggressiveness. This research also proves that liquidity has no effect on tax aggressiveness. Another finding is that profitability is able to moderate capital intensity on tax aggressiveness, while liquidity on profitability tax aggressiveness is not a moderating variable